Conformational evolution of soybean protein-polysaccharide at oil–water interface in simulated gastric environment in vitro. (1st July 2023) - Liu, Xiulin; Wang, Shengnan; Li, Yangyang; Yang, Lina; Liu, He; Song, Hong; Zhang, Guangchen
Graphical abstract: Highlights: The conformational evolution of SPI/SHP at interface in SGFWS was studied. The droplets only flocculated in SGFWS without significant change in size. Protonation and ion coupling make the drops flocculation most significant at 60 min. SPI/SHP emulsions deliver hydrophobic functional factors in SGFWS. Abstract: The conformation and characteristics of soybean hull polysaccharide (SHP)/soy bean protein isolate (SPI) complex at oil–water interface in simulated gastric environment in vitro were discussed. Isothermal titration calorimetry (ITC) thermodynamic results illustrated that SPI formed a complex with SHP. ζ-potential and microstructure showed a flocculation phenomenon after SPI/SHP emulsion droplet treatment (especially at 60 min), which indicated that the inter droplet steric hindrance and repulsion were reduced after the emulsion was treated. Additionally, at 60 min, in FT-IR spectrum fitting results, the contents of β -sheet and β -turn structure were the lowest, which might be that the polar group residues exposed in the SPI/SHP complex at the interface interacted with Na + by ion–dipole interaction or protonated with H + . The blue shift of maximum absorption intensity also indicated that the tryptophan residues moved to the hydrophobic environment, which made the treated droplets flocculate without obvious aggregation.